Optimization of Antibacterial Edible Film Formulation Based on Chitosan, Velvet Bean Ethanol Extract, and Cinnamon Essential Oil - Ariani, Sri Retno Dwi; Rohmatun, Tyas Dwi; Susilowati, Endang; Setyowati, Widiastuti Agustina Eko; Munifah, Ifah; Sholihah, Khoirur Rohmaniatush (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2024)
The existing research on edible films as packaging materials has maintained that they are better in constituent materials, composition, and functionality. Due to their good bioactivity, edible films are utilized for packaging, which is considered bioactive. The recent study focused on using chitosan-velvet bean (Mucuna pruriens (L.) DC.) based edible bioactive packaging formulation for antibacterial activity. Velvet bean ethanol extract (V) accompanied by cinnamon (Cinnamomum burmannii (Ness) BL) essential oil (C) which is effective as an antibacterial against Escherichia coli ATCC 25922 and Staphylococcus aureus ATCC 25923. Based on this study, the ascertained concentrations of V and C can generate the most optimum edible film associated with antibacterial activity and characterize the physical properties and morphology of the most optimum formulation of antibacterial edible film. It was proved that by addition of 30% V and 3.0% C, the most optimum edible film can be produced, which has maximum antibacterial activity against E. coli ATCC 25922 (19.36 mm strong) and S. aureus ATCC 25923 (18.94 mm strong). Moreover, this formulation boosts the thickness, tensile strength, and solubility of the film and simultaneously reduces the film's elongation, WVTR, and WVP. The edible bioactive packaging formulation produced thickness, tensile strength, solubility, percentage elongation, WVTR, and WVP values of 0.179 mm, 0.318 Mpa, 0.057%, 10.096%, and 3.747 g/m2.d, 8.586 g/m.d, respectively. The surface of the edible film still had some degree of porosity and texture, according to the morphology.